A Notch positive feedback in the intestinal stem cell niche is essential for stem cell self‐renewal. Issue 4 (April 2017) - Chen, Kai‐Yuan; Srinivasan, Tara; Tung, Kuei‐Ling; Belmonte, Julio M; Wang, Lihua; Murthy, Preetish Kadur Lakshminarasimha; Choi, Jiahn; Rakhilin, Nikolai; King, Sarah; Varanko, Anastasia Kristine; Witherspoon, Mavee; Nishimura, Nozomi; et al.
Abstract: The intestinal epithelium is the fastest regenerative tissue in the body, fueled by fast‐cycling stem cells. The number and identity of these dividing and migrating stem cells are maintained by a mosaic pattern at the base of the crypt. How the underlying regulatory scheme manages this dynamic stem cell niche is not entirely clear. We stimulated intestinal organoids with Notch ligands and inhibitors and discovered that intestinal stem cells employ a positive feedback mechanism via direct Notch binding to the second intron of the Notch1 gene. Inactivation of the positive feedback by CRISPR/Cas9 mutation of the binding sequence alters the mosaic stem cell niche pattern and hinders regeneration in organoids. Dynamical system analysis and agent‐based multiscale stochastic modeling suggest that the positive feedback enhances the robustness of Notch‐mediated niche patterning. This study highlights the importance of feedback mechanisms in spatiotemporal control of the stem cell niche. Synopsis: A direct positive feedback loop, in which the intracellular domain of activated Notch receptors binds to an enhancer in the second intron of the Notch1 gene to enhance its expression, is critical for intestinal stem cell self‐renewal and niche patterning. Characterization of the Notch signaling response using intestinal organoids shows that the activated Notch receptor binds to an enhancer site in the second intron of the Notch1 gene to form a positive feedback loop in the intestinal stem cell. The Notch1 positive feedback loop is essential for intestinal regeneration and stem cell self‐renewal. Computational modeling indicates that the Notch1 positive feedback enhances robustness of stem cell niche patterning. Abstract : A direct positive feedback loop, in which the intracellular domain of activated Notch receptors binds to an enhancer in the second intron of the Notch1 gene to enhance its expression, is critical for intestinal stem cell self‐renewal and niche patterning.